Deus ex : Icarus effect - Swallow, James (Del Rey/Ballantine Books Trade Paperbacks, 2011)
It's not the end of the world ... but you can see it from here. The year is 2027. In a world consumed by chaos and conspiracy, two people are set on a collision course with the most powerful and dangerous organization in history-- and the fate of humanity hangs in the balance.